2022
DOI: 10.3390/ijerph19159591
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Pandemic and Consumption of Dietary Supplements among Adult Residents of Lithuania

Abstract: In the light of the changing pattern of the consumption of dietary supplements among adults in other countries during the COVID-19 pandemic, we aim to assess the prevalence of the consumption of dietary supplements with respect to the purpose of consumption and sociodemographic factors among adults in Lithuania. This study included two samples of adults from Lithuania: 870 in 2019 and 1600 in 2021. Anonymous original questionnaires were used to collect the data about the consumption of dietary supplements befo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 15 publications
2
19
0
1
Order By: Relevance
“…However, even though the usage rates vary by country and the period of data collection (in relation to the COVID-19 pandemic), a comparison with different studies is difficult because the usage rates vary by the defined usage timeframe. Thus, before the pandemic, similar studies revealed high percentages of history of DS use (e.g., Switzerland 53% [ 26 ] and Saudi Arabia 63.2% [ 16 ]); meanwhile, others examined DS usage using a relatively wide usage timeframe, such as during the last one or two years (e.g., Spain: 9.3% [ 7 ], Poland: 10% [ 8 ], France: 40.8% [ 27 ], Italy: 49% [ 22 ], Netherlands: 62% [ 18 ] and Lithuania: 66.1% [ 9 ]) or a narrower range, such as during the previous week/month (e.g., France: 24.8% [ 27 ], Greece: 31.4% [ 12 ], Australia: 43.2% [ 28 ], Denmark: 55.8% [ 21 ] and USA: 57.6% [ 29 ]). Indeed, many studies have shown an increase in DS use after the pandemic began (e.g., Spain: 21.3% [ 10 ], Poland: 48–79% [ 11 ] and Lithuania: 78.1% [ 9 ]), with Greece, however, showing mixed results [ 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, even though the usage rates vary by country and the period of data collection (in relation to the COVID-19 pandemic), a comparison with different studies is difficult because the usage rates vary by the defined usage timeframe. Thus, before the pandemic, similar studies revealed high percentages of history of DS use (e.g., Switzerland 53% [ 26 ] and Saudi Arabia 63.2% [ 16 ]); meanwhile, others examined DS usage using a relatively wide usage timeframe, such as during the last one or two years (e.g., Spain: 9.3% [ 7 ], Poland: 10% [ 8 ], France: 40.8% [ 27 ], Italy: 49% [ 22 ], Netherlands: 62% [ 18 ] and Lithuania: 66.1% [ 9 ]) or a narrower range, such as during the previous week/month (e.g., France: 24.8% [ 27 ], Greece: 31.4% [ 12 ], Australia: 43.2% [ 28 ], Denmark: 55.8% [ 21 ] and USA: 57.6% [ 29 ]). Indeed, many studies have shown an increase in DS use after the pandemic began (e.g., Spain: 21.3% [ 10 ], Poland: 48–79% [ 11 ] and Lithuania: 78.1% [ 9 ]), with Greece, however, showing mixed results [ 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have also generated significant percentages supporting similar views in individuals both with and without a health science background [ 16 , 30 , 31 , 32 , 33 , 34 ]. In fact, studies have shown that during the pandemic a certain disease preventative/treatment mindset was shaped amongst many consumers, as they had made a connection between the enhancement of their immune system and DS consumption [ 9 , 11 , 13 , 20 , 35 , 36 , 37 , 38 , 39 ]; meanwhile, the current literature does not currently advise for or against the use of DS against the prevention or the treatment of COVID-19 [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations